(untitled) (The Journal of Economic Concerns, 2025)
The study was carried out to examine the performance of women entrepreneurs, using the crosssectional research design. Information was collected from 101 women entrepreneurs from three key entrepreneurial domains: manufacturing, trading, and services activities of micro, small and medium-scale businesses. The ordinal logistic regression was calculated to investigate the factors affecting the performance of women entrepreneurs in the study. The study found that feasibility studies, total investment, age, overhead cost, and loans significantly affect the performance of women entrepreneurs. Likewise, most of the women entrepreneurs in the study were satisfied with their sales turnover, profit, and income. The study recommends providing easy loan facilities and tax exemptions for the women entrepreneurs for promoting their participation and efficiency. Additionally, feasibility studies should be encouraged before starting the operation of any business.